The Triomathematics, Trithmetic, Trichometry, Triangulus & Ternary Algebra Expressions that Define the Triophysics and Triological Sciences Related to the Triscalar Mitigation of Non-Ionized Radiation via Bioharmonic Biobalancing Healthy Smart Solar Nanob - Osler II, James Edward Osler II (Advances in Social Sciences Research Journal, 2021)
The narrative in this paper provides a detailed and descriptive mathematical model for operative Healthy Smart Solar Nanobiotechnology ™ © (Osler, 2021) designed to biobalance a non-ionized irradiated environment. The in-depth mathematics mentioned in this paper are the foundational elements for groundbreaking innovative terminologies and new pioneering scientific fields covered in detail to explicitly explain how Healthy Smart Solar Nanobiotechnology ™ © interacts with and works within the environment. These revolutionary fields of study are directly associated with the mitigating mathematical operation of Solar Smart Nanobiotechnology ™ ©. The mathematics defined in the paper also aid in the creation of new, novel, and original areas and arenas of knowledge that are designed to most accurately describe the trichotomous holistic solutions that can be used to create an all around healthy and safe environment for the well-being of all.